Suitability of Hybrid Acacia Wood for Manufacturing Plywood and Particleboard - Rahaman, MM; Akhter, K; Biswas, D; Sheikh, MW (Journal of Bangladesh Academy of Sciences, 2012)
Hybrid acacia, produced from natural crossing between two introduced timber species Acacia mangium and A. auriculiformies has been studied for assessing the suitability of plywood and particleboard manufacture. It was found that 1.5 mm thick smooth and figured veneer can be made and dried easily. Three-ply plywood were made using veneer of this species bonded with liquid urea formaldehyde glue of 50% solid content extended with wheat flower and catalyzed (ammonium chloride) with 2% hardener under the specific pressures, viz., 1.05, 1.40 and 1.76 N/mm2 in three replications at 6 minute press time and 120°C press temperature. Dry and wet shear test were conducted on the sample and their shear load at failure per unit area and percentage of wood failure were determined. 1.76 N/mm2 pressure for the manufacture of ply wood is found to be the best. The particleboard was tested for determining the strength and dimensional stability. The bending strength passed the standard specification, tensile strength was found to be low as per Indian standard. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12960 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 171-176, 2012